First species of Ctenisomorphus Raffray, 1890 from China, with comments on Largeyeus J.-K. Li, 1993 (Coleoptera, Staphylinidae, Pselaphinae) - Li, Qi-Qi; Wang, Yan; Yin, Zi-Wei (Zootaxa, 2021)
The Ctenistini fauna of China is insufficient documented. In this paper the first Chinese species of the genus Ctenisomorphus Raffray, 1890, C. yinggelingensis sp. nov., is described and separated from congeners based on two male and four female specimens collected at Yinggeling Natural Reserve, Hainan Island, southern China. Images of the habitus and major diagnostic characters of the new species are provided. The taxonomic status of Largeyeus anhuianus J.-K. Li, 1993 distributed in Anhui, eastern China is discussed, and the genus is placed as a junior synonym of Poroderus Sharp, 1883 syn. nov., resulting in P. anhuianus comb. nov.